Marketing Public Relations Strategy Ganie Radio 93.3 FM Simalungun in Attracting the Interest of Advertisers - Dina Evi Rahmi; Nurhanifah Nurhanifah; Yaumi Saidah; Ghita Irwanty; Fatimah Zuhra; Marwah Hardini (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
Today's media landscape is evolving rapidly. To compete successfully, a radio company must develop its strategy and policy direction. The combination of concepts between marketing and public relations becomes a solution to find customers to advertise their products on the radio to overcome various problems faced in the increasingly complicated world of media where business competition is getting tougher. Ganie Radio 93.3 FM Simalungun has a marketing department that is also in charge of public relations. Ganie Radio 93.3 FM Simalungun can also be said to have never been without advertisements, even though there were not too many advertisements. However, Ganie Radio 93.3 FM Simalungun still exists today. Based on the background, the formulation of this study is to determine the marketing public relations strategy of Ganie Radio 93.3 FM Simalungun in attracting advertisers' interest. Data collection techniques in this study are by conducting in-depth interviews, observation, and documentation. By using qualitative descriptive data analysis. The informants interviewed were the marketing manager for Ganie Radio 93.3 FM Simalungun and the marketing staff for Ganie Radio 93.3 FM Simalungun.